Afterword: a critical reckoning with the 'Asian Century' in the shadow of the anthropocene. Issue 4 (1st July 2021) - Oakes, Tim
Abstract: What does the advent of an 'Asian Century' portend for critical tourism geographies? This commentary argues that two recent developments have made a critical reckoning with the Asian Century more pressing than ever. First, the Asian Century is in danger of being eclipsed by the deteriorating relationship between China and the United States. And second, the COVID-19 pandemic has created unprecedented challenges for tourism throughout the world and threatens to fundamentally upend travel as we've known it for the foreseeable future. These two developments suggest a pressing need not just for a decentering of Eurocentric approaches in tourism scholarship - as has long been argued by critical tourism scholars - but for a more thorough unraveling of the politics of knowledge in tourism scholarship.